A novel sulfur dioxide probe inhibits high glucose-induced endothelial cell senescence - Ren, Hui; Han, WenWen; Wang, Shuo; Zhao, BaoXiang; Miao, JunYing; Lin, ZhaoMin (Frontiers in Physiology, 2022)
Sulfur dioxide (SO2) is an important gas signal molecule produced in the cardiovascular system, so it has an important regulatory effect on human umbilical vascular endothelial cells (HUVECs). Studies have shown that high glucose (HG) has become the main cause of endothelial dysfunction and aging. However, the mechanism of by which how SO2 regulates the senescence of vascular endothelial cells induced by HG has not yet been clarified, so it is necessary to find effective tools to elucidate the effect of SO2 on senescence of HUVECs. In this paper, we identified a novel sulfur dioxide probe (2-(4-(dimethylamino)styryl)-1,1,3-trimethyl-1H-benzo[e]indol-3-ium, DLC), that inhibited the senescence of HUVECs. Our results suggested that DLC facilitated lipid droplets (LDs) translocation to lysosomes and triggered upregulation of LAMP1 protein levels by targeting LDs. Further study elucidated that DLC inhibited HG-induced HUVECs senescence by promoting the decomposition of LDs and protecting the proton channel of V-ATPase on lysosomes. In conclusion, our study revealed the regulatory effect of lipid droplet-targeted sulfur dioxide probes DLC on HG-induced HUVECs senescence. At the same time, it provided a the new experimental evidence for elucidating the regulatory mechanism of intracellular gas signaling molecule sulfur dioxide on vascular endothelial fate.